Diverse reprogramming codes for neuronal identity - Tsunemoto, Rachel; Lee, Sohyon; Szűcs, Attila; Chubukov, Pavel; Sokolova, Irina; Blanchard, Joel W.; Eade, Kevin T.; Bruggemann, Jacob; Wu, Chunlei; Torkamani, Ali; Sanna, Pietro Paolo; Baldwin, Kristin K. (Nature (London), 2018)
The transcriptional programs that establish neuronal identity evolved to produce the rich diversity of neuronal cell types that arise sequentially during development. Remarkably, transient expression of certain transcription factors can also endow non-neural cells with neuronal properties. The relationship between reprogramming factors and the transcriptional networks that produce neuronal identity and diversity remains largely unknown. Here, from a screen of 598 pairs of transcription factors, we identify 76 pairs of transcription factors that induce mouse fibroblasts to differentiate into cells with neuronal features. By comparing the transcriptomes of these induced neuronal cells (iN cells) with those of endogenous neurons, we define a ‘core’ cell-autonomous neuronal signature. The iN cells also exhibit diversity; each transcription factor pair produces iN cells with unique transcriptional patterns that can predict their pharmacological responses. By linking distinct transcription factor input ‘codes’ to defined transcriptional outputs, this study delineates cell-autonomous features of neuronal identity and diversity and expands the reprogramming toolbox to facilitate engineering of induced neurons with desired patterns of gene expression and related functional properties. A screen in which combinatorial pairs of transcription factors are exogenously expressed in fibroblasts identifies different combinations that reprogram these cells into induced neuronal cells with diverse functional properties.